Molecular dynamics simulation of water-based Ferro-nanofluid flow in the microchannel and nanochannel: effects of number of layers and material of walls - Xiao, Yong Shen; Hekmatifar, Maboud; Abd Shukor, Mohd Yunus; Alizadeh, As'ad; Yu, Liang Sun; Toghraie, Davood; Sabetvand, Roozbeh (Elsevier BV, 2021)
Due to the increasing development of nanotechnology and its wide applications, the flow of a nanofluid in a duct is also optimal geometric construction of ducts in the fabrication and production of various ducts to increase efficiency in nanofluid behavior are essential. In this paper, by using the molecular dynamics (MD) simulation process, the effect of Fe3O4 nanoparticles on the behavior of water-based fluid is investigated. Physical parameters such as total temperature, potential energy, fluid, nanofluid density profiles, fluid velocity, nanofluid profiles, and fluid and nanofluid temperature profiles are reported. Also, the effect of the number of layers and wall material on fluid flow is investigated. Therefore, the channel wall material in the following simulations will be considered as platinum, copper, and iron. Over time, the temperature of atomic structures reaches 300 K, which indicates the temperature stability in the simulated atomic structures. The results show that by increasing the number of wall layers in nanochannels and similar microchannels, interactions between fluid particles and walls increase. As these interactions increase, the accumulation of fluid particles in the vicinity of the channel walls increases, which increases the density of the shelves adjacent to the channel walls. Also, by changing the microchannel material from copper to iron and platinum, the number of interactions between particles in the present structures increases. This increase in the number of interactions between the particles present in the microchannel wall and the base fluid causes the maximum density to be observed in the platinum microchannel.